Intelligent Agricultural Systems Advisory Tool (iSAT) - Kumar, Shalander; Jat, Mangi L.; Kumar, Kishore G.; Roa, K.P.C. (International Crops Research Institute for the Semi-Arid Tropics, 2024)
Farmers in the Global South, especially smallholders face numerous challenges like climate variability and change, despite their critical role in ensuring food security, their adoption of climate-smart agricultural practices remains low. Mainly due to lack of awareness and access to digital tools and technologies, most of the farmers do not have access to location specific climate information and context specific decision making tools that equip them to identify and plan the best farming strategies and practices for their individual farms which directly impacts their productivity and livelihoods. Recognizing this opportunity, ICRISAT and its partners have developed and piloted a digital platform Intelligent Agricultural Systems Advisory Tool (iSAT) that serves as a one stop solution centre for all issues related to climate, weather and agro-advisories.